Skin delivery of antioxidant surfactants based on gallic acid and hydroxytyrosol. (3rd February 2015) - Alonso, Cristina; Lucas, Ricardo; Barba, Clara; Marti, Meritxell; Rubio, Laia; Comelles, Francesc; Morales, Juan Carlos; Coderch, Luisa; Parra, José Luís
Abstract Objectives The aim of this study has been to investigate the dermal absorption profile of the antioxidant compounds gallic acid and hydroxytyrosol as well as their derivatives, hexanoate (hexyl gallate and hydroxytyrosol hexanoate) and octanoate (octyl gallate and octanoate derivative) alkyl esters (antioxidant surfactants). Previously, the scavenging capacity of these compounds, expressed as efficient dose ED50, has also determined. Methods The percutaneous absorption of these compounds was obtained by an in vitro methodology using porcine skin biopsies on Franz static diffusion cells. The antiradical activity of compounds was determined using the 1, 1‐diphenyl‐2‐picrylhydrazyl free radical method. Key findings The percutaneous penetration results show the presence of antioxidants in all layers of the skin. The content of the cutaneously absorbed compound is higher for the antioxidant surfactants (ester derivatives). This particular behaviour could be due to the higher hydrophobicity of these compounds and the presence of surface activity in the antioxidant surfactants. Conclusions These new antioxidant surfactants display optimum properties, which may be useful in the preparation of emulsified systems in cosmetic and pharmaceutical formulations because of their suitable surface activity and because they can protect the skin from oxidative damage.